The Microsoft Data Warehouse Toolkit: With SQL Server 2005 and the Microsoft Business Intelligence Toolset - Mundy (Joy); Thornthwaite (Warren); Kimball (Ralph) (2006)
Data Warehousing
22.5
Keywords: Data Warehousing